On Monads and Substantivities. Or Leibniz and Zubiri - Diego Gracia (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The risk of understanding incorrectly authors raises to the same extent as they are innovative. The context of reading and understanding innovative texts cannot be other than the traditional or previous to the innovation, that in which the technical language of the discipline was coined. This language is also the one used by the innovator, fulfilling the old words with new meanings. The consequence being that the more natural way of understanding innovative texts is always to interpret them into the framework of the traditional received categories, loosing all its originality. This is quite apparent in the case of Zubiri's philosophy, which has been frequently interpreted with the categories usual in the rationalistic tradition of Western philosophy. This article attempts to clarify this point, confronting the pure reason of Leibniz with the sentient or impure intelligence of Zubiri. These are two different ways of understanding thought and reality, and therefore philosophy